7-Tesla MRI demonstrates absence of structural lesions in patients with vestibular paroxysmia - Rommer, Paulus S.; Wiest, Gerald; Kronnerwetter, Claudia; Zach, Heidemarie; Loader, Benjamin; Elwischger, Kirsten; Trattnig, Siegfried (Frontiers in Neuroanatomy, 2015)
Vestibular parxoysmia is rare vestibular disorder. A neurovascular cross-compression between the vestibulochochlear nerve and an artery seems to be responsible for short attacks of vertigo in this entity. A neurovascular cross-compression can be seen in up to every fourth subject. The significance of these findings is not clear, as not all subjects suffer from symptoms. The aim of the present study was to assess possible structural lesions of the vestibulocochlear nerve by means of high field magnetic resonance imaging (MRI), and whether high field MRI may help to differentiate symptomatic from asymptomatic patients. 7 Tesla MRI was performed in six patients with vestibular paroxysmia and confirmed neurovascular cross-compression seen on 1.5 and 3.0 MRI. No structural abnormalities were detected in any of the patients in 7 Tesla MRI. These findings imply that high field MRI does not help to differentiate between symptomatic and asymptomatic neurovascular cross-compression and that the symptoms of vestibular paroxysmia are not caused by structural nerve lesions. This supports the hypothesis that the nystagmus associated with vestibular paroxysmia has to be conceived pathophysiologically as an excitatory vestibular phenomenon, being not related to vestibular hypofunction. 7 Tesla MRI outperforms conventional MRI in image resolution and may be useful in vestibular disorders.